Demonstrating the role of anchoring functionality in interfacial electron transfer dynamics in newly synthesized BODIPY-TiO2 nanostructure composite - Ghosh, Hirendra N.; Das, Amitava; Aute, Sunil; Maity, Partha (New Journal of Chemistry, 2017)
New Bodipy derivatives (Dye 1 and 2) having catechol or resorcinol functionality for anchoring to the nanostructured (NS) TiO2 surfaces have been synthesized. Extended conjugation at one of the two pyrrole rings at the C3 position has helped us in achieving the desired control in tuning the optical and redox properties of the BODIPY based dye molecules. Relative emission quantum yields (em1 = ~52 ± 2% and em2 = 54 ± 2%) are found to be much higher in polar aprotic solvent (acetonitrile), while this are found to be substantially lower for dye 1 in polar protic solvent. Steady state optical absorption studies reveal the formation of a strong charge transfer complex between dye 1 and NS-TiO2, while this interaction is much weaker for dye 2. Transient absorption studies have been carried out for 1/NS-TiO2 and 2/NS-TiO2 systems following excitation with a laser source of 400 nm for understanding the charge transfer dynamics. Results of the transient absorption spectral studies helped in elucidating role of anchoring functionality in influencing the dynamics of the interfacial electron transfer and the charge recombination process in ultrafast time scale.